2003
DOI: 10.1055/s-2003-43265
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Fat Oxidation During Exercise in Trained Men

Abstract: [Aims] In the present study, we examined effects of exercise training (TR) on high fat diet (HFD)-induced expression changes of prothymosin α (ProTα) and its functions in white adipose tissue (WAT). [Methods] Eight-week-old male C57BL/6J mice were divided randomly into three groups: 1) C mice: control mice; 2) HFD mice: mice fed HFD (60% fat) for 4 months; 3) HFD-TR mice: mice fed HFD with voluntary TR on a running wheel for 4 months. We then investigated the expression of ProTα in WAT. Moreover, to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
101
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(117 citation statements)
references
References 24 publications
(47 reference statements)
10
101
3
1
Order By: Relevance
“…It is to note that interindividual variations of the maximal fat oxidation point were important with values ranging between 33% and 74% of % _ VO 2max m, a finding which is in agreement with a previous report Meyer et al 2007). These values are lower than the values of 80-85% _ VO 2max beyond which a high glycolytic flux is likely to decrease the bicarbonate pool and increase _ VO 2 due to the buffering of hydrogen ions (Achten and Jeukendrup 2003). A limit of the present study as well as well as several other studies (Achten and Jeukendrup 2003;Brandou et al 2003Brandou et al , 2005Brandou et al , 2006Lazzer et al 2007) measuring the maximal fat oxidation point during an incremental exercise is that we cannot exclude that short duration steps are too short to elicit a steady state of RER (Meyer et al 2007).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is to note that interindividual variations of the maximal fat oxidation point were important with values ranging between 33% and 74% of % _ VO 2max m, a finding which is in agreement with a previous report Meyer et al 2007). These values are lower than the values of 80-85% _ VO 2max beyond which a high glycolytic flux is likely to decrease the bicarbonate pool and increase _ VO 2 due to the buffering of hydrogen ions (Achten and Jeukendrup 2003). A limit of the present study as well as well as several other studies (Achten and Jeukendrup 2003;Brandou et al 2003Brandou et al , 2005Brandou et al , 2006Lazzer et al 2007) measuring the maximal fat oxidation point during an incremental exercise is that we cannot exclude that short duration steps are too short to elicit a steady state of RER (Meyer et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…These values are lower than the values of 80-85% _ VO 2max beyond which a high glycolytic flux is likely to decrease the bicarbonate pool and increase _ VO 2 due to the buffering of hydrogen ions (Achten and Jeukendrup 2003). A limit of the present study as well as well as several other studies (Achten and Jeukendrup 2003;Brandou et al 2003Brandou et al , 2005Brandou et al , 2006Lazzer et al 2007) measuring the maximal fat oxidation point during an incremental exercise is that we cannot exclude that short duration steps are too short to elicit a steady state of RER (Meyer et al 2007). However, we used this procedure because it is far more practical for patients and experimenters than determining a maximal fat oxidation point during 30 min to 1 h constant load tests repeated several times within a few days (Meyer et al 2007).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Previous studies have shown that maximal fat oxidation often occurs during approximately 50% _ VO 2 max exercise for general population (Venables et al 2005;Achten and Jeukendrup 2004). When exercise intensity further increases, fat oxidation decreases, whereas CHO oxidation is markedly increased (Achten and Jeukendrup 2003;Romijn et al 1993). Therefore, moderate intensity exercise appears to be the most favorable for eliciting a substantial short-term increase in fat oxidation.…”
Section: Introductionmentioning
confidence: 96%
“…It is well described that fat oxidation rates peak at ∼60% to 65% of maximal oxygen consumption (VO 2 max) and once blood lactate is accumulating, fat metabolism dramatically diminishes and may be negligible above 90% of VO 2 max in favour of carbohydrate to fuel a high ATP turnover and maintain workload. 85 This has significant implications for glycogen use, recovery duration and, therefore, EB. Furthermore, training at altitude or in the heat will further increase glycogen turnover and decrease exercise efficiency, 86 as will training in a fatigued or depleted state.…”
Section: Despite a Periodmentioning
confidence: 99%